インプラント周囲の歯槽骨頂部に骨増生を認めた ビスフォスフォネート治療患者の3症例 - 小澤, 重雄; 金子, 昌豊; 又賀, 泉; 根岸, 邦雄; 渡沼, 敏夫 (Journal of Japanese Society of Oral Implantology, 2015)
The present report describes abnormal bone hyperplasia at the alveolar crest between implants placed around the mandibular molar area in three patients who have been medicated with bisphosphonate for osteoporosis. All three patients were female, and were aged 66, 68 and 67 years old. They complained of difficulty of brushing beneath the superstructure of implants. Dental radiography showed a band-like radiopacity at the alveolar bone crest between the mandibular molar implants. They were diagnosed with bone hyperplasia in the mandible. The lesion was surgically resected under local anesthesia after removing the superstructure in 2 of 3 patients, and sclerosis and normal bone tissue were observed histologically. These findings highlight the need for clinicians to monitor patients receiving bisphosphonate therapy.